Effects of electrophoresis buffer, electrophoresis time, and annealing temperature on the quality of SSR molecular detection in rice varieties - Zheng Liang; Chenglong Pan; Zongjun Zhang; Yang Wang; Min Liu; Peisong Chen; Jingrou Chen (Cogent Food & Agriculture, 2023)
AbstractSSR (simple sequence repeat) is a common molecular marker widely used in the analysis of rice genome and genetic variation research. While there have been some reports on factors affecting the quality of SSR molecular detection, no one has comprehensively explained these factors to date. Therefore, this study explores in detail the effects of electrophoresis buffer, electrophoresis time, and annealing temperature on the quality of SSR molecular detection in rice varieties. The results show that freshly prepared electrophoresis buffer, appropriate electrophoresis time, and suitable annealing temperature can improve the quality of SSR molecular detection in rice varieties and provide important technical support for in-depth research on the rice genome. Moreover, it is recommended that laboratories select and combine the aforementioned optimal experimental conditions to enhance the authenticity of rice varieties and improve the accuracy of molecular detection for purity.